Diagnosis of a severe congenital anomaly: A qualitative analysis of parental decision making and the implications for healthcare encounters. (2nd February 2018) - Lotto, Robyn; Smith, Lucy K.; Armstrong, Natalie
Abstract: Objective: To explore parental decision making following diagnosis of a severe congenital anomaly, and implications for healthcare encounters. Design: Qualitative semi‐structured interviews with 38 parents‐to‐be were collated and triangulated with data generated from consultation recordings. Analysis: Data were analysed using a constant comparative‐based approach. Setting: Recruitment was undertaken across four fetal medicine sites in two tertiary referral trusts. Participants: Parents‐to‐be whose pregnancy was suspected or diagnosed as being affected by a severe congenital anomaly. This sample was purposive to include known factors affecting the decision to terminate or continue the affected pregnancy. Findings: In trying to make a decision about how to proceed with their pregnancy, parents‐to‐be typically had to work hard to negotiate multiple uncertainties around the diagnosis and prognosis of the suspected anomaly. This was influenced by parents' capacity to cope with uncertainty and the way in which uncertainty was managed by the clinical team. This negotiation of uncertainty was enacted within a fluid, nonlinear three‐phase process: "information seeking, " reflecting the way parents‐to‐be face the uncertainty associated with a fetal diagnosis and associated prognosis; "implications, " where consideration is given to future consequences of the decision; and "decision making, " which reflects the way in which the decision is made (head‐ or heart‐led). Spectrums of responses were apparent within each phase. Conclusions: This study provides important insights into how parents‐to‐be make decisions following diagnosis or suspicion of a severe congenital anomaly. The impact of these on healthcare encounters is discussed, alongside recommendations for clinical practice.